A HCBP1 peptide conjugated ruthenium complex for targeted therapy of hepatoma. Issue 4 (2nd January 2020) - Wang, Yi; Qin, Weirong; Shi, Hongdong; Chen, Haijie; Chai, Xiaoyan; Liu, Jingang; Zhang, Pingyu; Li, Zigang; Zhang, Qianling
Abstract : An HCBP1 peptide–ruthenium conjugate (Ru–β-Ala-FQHPSFI) as a potential candidate for targeted therapy of hepatoma was synthesized. Abstract : An HCBP1 peptide–ruthenium conjugate (Ru–β-Ala-FQHPSFI) as a potential candidate for targeted therapy of hepatoma was synthesized. Ru–β-Ala-FQHPSFI shows drastically enhanced cytotoxicity and high selectivity for hepatoma cells versus noncancer liver cells. Raman imaging shows that this peptide-based drug can be taken up well by the hepatoma cells compared with the bare ruthenium complex (Ru) and the opposite sequence peptide–ruthenium conjugate (Ru-β-Ala-IFSPHQF). This study presents a new strategy for the construction of tumor-targeting metal-based anticancer therapeutics.